SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN SANTRI TELADAN MENGGUNAKAN METODE AHP BERBASIS WEB - Rizal Ghozali , Wahyu; Lazulfa , Indana (Inovate, 2024)
In determining the order of model students, it is very difficult because there is no system that helps in making decisions. So that this does not happen, a model is used that can help decision makers to determine superior students according to the criteria set by Islamic boarding schools. A Decision Support System (DSS) is a system it is intended to be a tool for decision makers to improve their skills, but not to influence their judgment. DSS are intended for decisions that require judgment or cannot be supported by algorithms at all.. The process of selecting who is entitled to receive the title of model students and get a scholarship at the Darul Qowaid Islamic Boarding School still experiences problems in the decision-making process. The purpose of this study is to create a web-based decision support system using the Analytical Hierarchy Process (AHP) method, as there is currently no objective way to quickly determine scholarship eligibility based on available data.The results of this study are that the application of a decision support system for selecting model students with the AHP method has succeeded in determining the final result or decision result issued by the system. Keywords: Model Student, Analytical Hierarchy Process (AHP), Decision Support System, Web.